Quand l’aléa devient la ressource : l’activité d’extraction des matériaux volcaniques autour du volcan Merapi (Indonésie) dans la compréhension des risques locaux - Édouard de Bélizal; Franck Lavigne; Delphine Grancher (Cybergeo)
The valleys of the Merapi volcano are regularly filled with thick pyroclastic and volcaniclastic deposits, characterised by a large grain-size distribution, from fine ash to boulders. An important but quite informal mining of these materials (sands and blocks) has developed, and has become widespread around the volcano. It is now an essential activity in the spatial organisation of the Merapi volcano, and seems to play a major role in the local socio-economic pattern. Volcanic hazards such as pyroclastic flows or lahar flows produce a substantial resource which endangers people who dig these deposits. But the important benefits related to this activity encourage people to work in hazard-prone areas. Moreover, at a broader scale, block and sand mining generates many interactions and retroactions which seem to be a real factor of vulnerability for Merapi’s surrounding communities. Thus, this activity has to be taken into account when conducting risk and vulnerability studies around the volcano. They also help to better understand how people live and work there, and why most of them choose to stay and work even during intense volcanic activity.